First Impression Formation Allows Judgements in Regard to Coping in Life Rather than Subjective Well-Being - Linden, Michael; Keller, Laila; Noack, Nils (Journal of Psychology and Psychotherapy Research, 2019)
Background/Aims: Persons elicit emotional reactions in their vis-à-vis within a split-second, resulting in far reaching judgements. This is called first impression formation. It has been shown that respective judgements show high reliability. Data are needed on the validity. In this study we wanted to test, if it is possible to predict by first impression formation how a person feels and whether he or she has problems in life. Method: We invited a convenience sample of 102 train passengers to answer a short self-rating questionnaire on their present well-being and problems in life. Additionally, a researcher recorded her first impression of the passenger by using the MED scale. The researcher did not know the other person before. Results: Judgements on the impression of participants were unrelated to their present well-being. There were relations between a kind and friendly first impression formation and work-related problems and capacity restrictions in contrast to participants with a self-assured and over-confident appearance, who reported less problems with their abilities and the workplace. A friendly first impression formation was significantly more pronounced in females. Conclusion: Results suggest that first impression formation reflects not so much the present subjective inner status of the person but to some degree his or her personality and adjustment in life. This suggests that impression formation may be a factor which has a direct impact on coping with life, as persons communicate with others by their non-verbal behavior.